Probing the Limits of Egg Recognition Using Egg Rejection Experiments Along Phenotypic Gradients - Canniff, Lindsay; Dainson, Miri; López, Analía V; Hauber, Mark E; Grim, Tomáš; Samaš, Peter; Hanley, Daniel (Journal of visualized experiments, 2018)
Brood parasites lay their eggs in other females' nests, leaving the host parents to hatch and rear their young. Studying how brood parasites manipulate hosts into raising their young and how hosts detect parasitism provide important insights in the field of coevolutionary biology. Brood parasites, such as cuckoos and cowbirds, gain an evolutionary advantage because they do not have to pay the costs of rearing their own young. However, these costs select for host defenses against all developmental stages of parasites, including eggs, their young, and adults. Egg rejection experiments are the most common method used to study host defenses. During these experiments, a researcher places an experimental egg in a host nest and monitors how hosts respond. Color is often manipulated, and the expectation is that the likelihood of egg discrimination and the degree of dissimilarity between the host and experimental egg are positively related. This paper serves as a guide for conducting egg rejection experiments from describing methods for creating consistent egg colors to analyzing the findings of such experiments. Special attention is given to a new method involving uniquely colored eggs along color gradients that has the potential to explore color biases in host recognition. Without standardization, it is not possible to compare findings between studies in a meaningful way; a standard protocol within this field will allow for increasingly accurate and comparable results for further experiments.
Keywords: Ovum; ovum; ptáci; Birds; Animals; biologická evoluce; Female; ženské pohlaví; Biological Evolution; hnízdění; zvířata; Nesting Behavior